Astragaloside IV Alleviates H2O2-Induced Mitochondrial Dysfunction and Inhibits Mitophagy Via PI3K/AKT/mTOR Pathway - Miaomiao Qi; Qiongying Wang; Runmin Sun; Zeyi Cheng; Mingze Li; Xin Fan; Feng Bai; Jing Yu (Cardiovascular Therapeutics)
Oxidative stress and mitochondrial dysfunction play critical roles in the pathology of cardiovascular diseases. However, the effects of Astragaloside IV (As-IV) on mitochondrial function remain unclear. This study is aimed at evaluating the protective effects and mechanism of As-IV against H2O2-induced mitochondrial dysfunction in H9c2 cells. H9c2 cells were exposed to 200 μM H2O2 with or without As-IV. The level of apoptosis and reactive oxygen species (ROS) was measured by flow cytometry. Confocal microscopy and transmission electron microscopy were performed to detect the changes in mitochondrial membrane potential (MMP), mitochondrial morphology, and autophagosome. Mitochondrial dynamics and mitophagy-related proteins were measured by Western blot. The results indicated that As-IV decreased H2O2-induced apoptosis and ROS generation. Meanwhile, As-IV significantly increased MMP, exerted regulatory effects on mitochondrial dynamics, and ameliorated the damaged mitochondrial morphology in H2O2-injured cardiomyocytes. Additionally, As-IV decreased the amount of autophagosome and expressions of PINK1 and Parkin, but upregulated the expressions of PI3K, p-AKT, and p-mTOR proteins. However, cotreatment with LY294002 diminished the upregulation of PI3K, p-AKT, and p-mTOR induced by As-IV. In the study, we demonstrated that As-IV protected H9c2 cells from H2O2-induced mitochondrial dysfunction by inhibiting mitophagy, which might be related to the PI3K/AKT/mTOR pathway.